DEB-TACE combined with ici for advanced squamous cell carcinoma of the skin: a case report - Wu, Zhuo; Piao, Xuezhe; Kang, Dongxu; Jin, Lan; Xu, Qiang; Jin, Dehao; Piao, Longzhen (Frontiers in Oncology, 2025)
We report the case of an older female patient with squamous cell carcinoma of the skin, cTXN1M0, who initially presented with a mass of approximately 4.5 cm in diameter in the left temporal region, which had a tendency to break and bleed. Given the patient’s poor general status and ECOG score of grade 2, it was considered that she could not tolerate systemic chemotherapy. Therefore, we applied drug-eluting beads transarterial chemoembolization combined with immune checkpoint inhibitors to treat this patient and unexpectedly found that this regimen resulted in complete classified remission and in partial pathological response without significant adverse events.